1992
DOI: 10.1002/jnr.490320114
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin immunoreactivity in normal and duchenne human fetal neurons in culture

Abstract: Dystrophin, the protein product defective in Duchenne muscular dystrophy (DMD), is present in all types of muscle and in the brain. The function of the protein is unknown and its role in the brain is unclear, although 30% of DMD patients show nonprogressive mental retardation. We have therefore studied the localisation of dystrophin in cultures of normal and DMD human fetal neurons using antibodies raised to different regions of the protein. Dystrophin immunoreactivity was demonstrated in the soma and axon hil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
(28 reference statements)
0
18
0
Order By: Relevance
“…In astrocytoma Dp71f was found in the lamellipodia, with focal complexes, actin and integrin (Garcia-Tovar et al 2002). A similar pattern was observed in cultures of immature neurons (Mussini et al 1995;Torelli et al 1992). According to Garcia-Tovar et al (2001) Dys2 did not colocalize with the GFAP antibody, although it did with neurofilaments, whereas 5F3 immunoreactivity even in neurons does not co-localize with microtubules or intermediate filaments.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In astrocytoma Dp71f was found in the lamellipodia, with focal complexes, actin and integrin (Garcia-Tovar et al 2002). A similar pattern was observed in cultures of immature neurons (Mussini et al 1995;Torelli et al 1992). According to Garcia-Tovar et al (2001) Dys2 did not colocalize with the GFAP antibody, although it did with neurofilaments, whereas 5F3 immunoreactivity even in neurons does not co-localize with microtubules or intermediate filaments.…”
Section: Discussionmentioning
confidence: 56%
“…The results of Rowilski et al (1996) concur with this latter finding. In vitro, Torelli et al (1992) found that, in human cell culture, only neurons, not glial cells, were immunoreactive to dystrophin. Subcellular fractionation and ultrastructural studies have even revealed the binding of both full-length dystrophin and Dp71 to the cell membrane, including synaptic membranes (Jung et al 1993;Lidov et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…As Dp71d is the most abundant dystrophin short product in the brain, and seems to be associated with the cytoplasmic NF reticulum, its absence or a structural change of this protein in DMD patients may induce alterations in its subcellular distribution and interactions with NFs, as has been detected by Torelli et al (1992). This type of change may also contribute to alterations in the cognitive functions observed in some DMD patients.…”
Section: Discussionmentioning
confidence: 86%
“…It has been known that dystrophin exists in neuronal cells, but not in glial cells [21][22][23][24][25], Moreover, its localization is restricted to the plasma membrane of cell bodies and den drites, especially at the postsynaptic mem brane, but not in the axoplasm. Miike et al [16] firstly reported that the dystrophin ex isted in the OPL of mouse and rat retinas.…”
Section: Discussionmentioning
confidence: 99%